Navigating the New Antimicrobial Stewardship Regulations. Issue 8 (September 2017) - Davis, Sondra; Verheyden, Collin; Cooper, Mandelin; Desai, Devak
Purpose: Many health care facilities are navigating their way through the new antimicrobial stewardship standards and guidelines. The purpose of this article is to provide information for health care facilities to improve patient care.Summary: New regulations and guidelines surrounding antimicrobial stewardship have prompted facilities to review their process related to antimicrobial stewardship. In setting up a program, there are many factors to consider including involving key personnel, obtaining leadership support, identifying an infectious disease physician to chair or cochair the committee, and meeting agenda, metrics, and educational needs.Conclusion: Antimicrobial stewardship plays a vital role in both our hospital and community setting. Pharmacists are uniquely positioned to improve optimal patient care through rounding, review of patients' chart, and contribute to the improvement of antimicrobial stewardship by working with a multidisciplinary team. These efforts may improve the utilization of antimicrobial agents.